RNA trafficking in parasitic plant systems - LeBlanc, Megan L.; Kim, Gunjune; Westwood, James H. (Frontiers in Plant Science, 2012)
RNA trafficking in plants contributes to local and long-distance coordination of plant development and response to the environment. However, investigations of mobile RNA identity and function are hindered by the inherent difficulty of tracing a given molecule of RNA from its cell of origin to its destination. Several methods have been used to address this problem, but all are limited to some extent by constraints associated with accurately sampling phloem sap or detecting trafficked RNA. Certain parasitic plant species form symplastic connections to their hosts and thereby provide an additional system for studying RNA trafficking. The haustorial connections of Cuscuta and Phelipanche species are similar to graft junctions in that they are able to transmit mRNAs, viral RNAs, siRNAs and proteins from the host plants to the parasite. In contrast to other graft systems, these parasites form connections with host species that span a wide phylogenetic range, such that a high degree of nucleotide sequence divergence may exist between host and parasites and allow confident identification of most host RNAs in the parasite system. The ability to identify host RNAs in parasites, and vice versa, will facilitate genomics approaches to understanding RNA trafficking. This review discusses the nature of host parasite connections and the potential significance of host RNAs for the parasite. Additional research on host-parasite interactions is needed to interpret results of RNA trafficking studies, but parasitic plants may provide a fascinating new perspective on RNA trafficking.